2005
DOI: 10.1530/rep.1.00490
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-induced decrease in the relaxant effect of terbutaline in the late-pregnant rat myometrium: role of G-protein activation and progesterone

Abstract: The effectiveness of b 2 -agonists in preterm delivery is reduced by several factors. The aim of this study was to determine the influence of late pregnancy in the uterus-relaxing effect of terbutaline in the rat in vitro. Rat uterine tissues from late pregnancy (days 15, 18, 20 and 22) were used. In vitro electrical field-stimulation (EFS) was used to evoke contractions. The radioligand-binding technique, reverse transcription-polymerase chain reaction and radioimmunoassay technique were used to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
0
12
0
2
Order By: Relevance
“…Previous studies have found that sevofl urane reduces both the amplitude and frequency of myometrium contractions in myometrium isolated from humans [9,10] and rats [11,12]. Sevofl urane-induced myometrial relaxation has also been established using the AUC [13][14][15]. The failure to detect myometrial relaxation induced by sevofl urane via the amplitude or frequency in our study may be attributable to the small number of strips used.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Previous studies have found that sevofl urane reduces both the amplitude and frequency of myometrium contractions in myometrium isolated from humans [9,10] and rats [11,12]. Sevofl urane-induced myometrial relaxation has also been established using the AUC [13][14][15]. The failure to detect myometrial relaxation induced by sevofl urane via the amplitude or frequency in our study may be attributable to the small number of strips used.…”
Section: Discussionmentioning
confidence: 59%
“…The amplitude and frequency have traditionally been used as an index of myometrium contraction because they can be easily measured from analog data. Recently, new computer software has made it possible to calculate the AUC [13][14][15]. Previous studies have found that sevofl urane reduces both the amplitude and frequency of myometrium contractions in myometrium isolated from humans [9,10] and rats [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Although (Gaspar et al, 2005) found on the late stage of pregnancy the sensitivity of the uterus to β-adrenergic activity was weaker than the non-pregnant, unfortunately the progesterone treatment did not potentiate the β-receptors sensitivity to this fraction, these findings can be explained by that, the β-ADR only partially participated in this relaxation besides other possible mechanism(s) or may be hide by the presence of other compounds in this semi-purified fraction.…”
Section: Discussionmentioning
confidence: 67%
“…In spite that on this stage of pregnancy the sensitivity of the uterus to β-adrenergic activity was weaker than the non pregnant (Gaspar et al, 2005).…”
Section: Discussionmentioning
confidence: 72%
“…Estrogen enhances, while progesterone reduces the ability to contract (20). It was proved that the high plasma level of progesterone restores the function of β 2 -adrenergic receptors at the end of pregnancy (21). On the other hand, progesterone has anti-inflammatory effect that may have high physiological and therapeutic importance in the inflammatory approach to PD (22).…”
Section: Physiological Factors and Therapeutic Targets Of Pregnant Utmentioning
confidence: 99%